Analysis of the Application of Islamic Business Ethics to the Practice of Money Bouquet Transactions at Inart Gallery Shop - Nur'aini, Nike (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2025)
The rise of money bouquet sales in the Muslim community does not ensure that the money bouquet transactions carried out by Muslim entrepreneurs are in accordance with Islamic law. So it needs to be studied as a whole from a sharia perspective. The purpose of this research is to analyze the application of Islamic business ethics to the practice of money bouquet transactions at Inart Gallery Shop. The research method used is descriptive qualitative approach with case study design. The results of this study indicate that the practice of money bouquet transactions at Inart Gallery Shop has applied the principles of Islamic business ethics, namely running a business on the basis of tawhid to avoid usury transaction practices, maintaining justice in setting the price of money bouquet in accordance with the ijarah contract, giving freedom to buyers in choosing how to transact, a sense of responsibility for money bouquet orders, and upholding the principle of ihsan. Thus, the practice of money bouquet transactions at Inart Gallery Shop can be categorized as a form of shar'i buying and selling because it runs its business based on the principles of Islamic business ethics.